Aristotelian Scientific Method & Categorization Applied to Spirituality: Spiritual compassion, musical & artistic spiritu8ality, healing spiritual experiences in grief, Arctic humna relations, T'boli dream weaving, Medical research meta-analyses - Charles Peck Jr (2011)
From 40 years of experience it is clear that spirituality has become entangled in abstractions: powers, perfection, supernatural, unreal, limitless knowledge, crystal ball perceptions, etc. Dr Stephen Farra agreed with that – and went one better. Dr Farra stated “Our models are out reality. But our models are not reality. That coincides with the immortal philosopher Kant who argue we do not perceive the real world – but “representations” of the real world. Similarly, Bargh - from unconscious research - emphasizes mental categories and norms/stereotypes. Jung emphasizes symbols – which he argues are outside cognitive appraisals. The bottom line is that “models” - and how we envision the world - are not just pivotal – but vital. Aristotelian Scientific Method Applied to Spirituality – Counterpoint to the materialist maxim that "All spirituality is unreal" Aristotle described Scientific Method as 1. Gather the Facts 2. Categorize the Data 3. Analyze the Information 4. Draw Conclusions A proper categorization has not been done – here is a preliminary sketch – in context of William James Principle of “Practical Use!” That is the focus is “real world” spirituality counterpoint to the materialist maxim that "All spirituality is unreal" - I write about artistic spirituality, the spirituality of music (surprisingly, the spirituality of grieving, and dreams of the deceased which as one psychologist observed are not "unusual" and some studies demonstrate facilitate healing, the spirituality of compassion. Recently I have also written about dreams as a source of [divine inspiration and the T’boli (and Bla'an) dream weaving - which is known world-wide for textile creativity. With a comparison with categorization from the chapter, "Mystical, Spiritual, and Religious Experiences” – Park and Paloutzian’s Handbook 1. "UFO's and Alien abductions" 2. "Psychedelics or Entheogens" 3. Near-Death Experience 4. Numinous and Mystical Experiences.